2008
DOI: 10.1016/j.surneu.2008.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of chondroitinase ABC on sensory axon regeneration in a laceration model of spinal cord injury in the rat

Abstract: Background-Chondroitin sulfate proteoglycans (CSPGs) are upregulated in the spinal cord following spinal cord injury (SCI) creating a molecular barrier inhibitory to axon growth. Chondroitinase ABC (ChABC) degrades CSPGs in vitro and in vivo.Methods-We studied whether intrathecal (IT) ChABC promotes axonal regeneration in a laceration model of SCI. Three groups of Sprague Dawley rats were used: control and rats treated with low dose and high dose IT ChABC. CSPG breakdown products were measured by 2-B-6 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 62 publications
(81 reference statements)
1
28
0
3
Order By: Relevance
“…So far, few studies have addressed the impact of ChABC treatment on astrocyte morphology, and none reported any relevant influence on scar formation, 57,58 excepting the work of Chau and colleagues, 59 who combined ChABC treatment with Schwann cell grafts, which resulted in a decrease of GFAP labeling and stimulation of astrocytic processes entering the graft tissue. Our present study clearly demonstrates that treating the injured spinal cord with ChABC alone was sufficient to achieve the modification of the astrocytic reaction described by Chau and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…So far, few studies have addressed the impact of ChABC treatment on astrocyte morphology, and none reported any relevant influence on scar formation, 57,58 excepting the work of Chau and colleagues, 59 who combined ChABC treatment with Schwann cell grafts, which resulted in a decrease of GFAP labeling and stimulation of astrocytic processes entering the graft tissue. Our present study clearly demonstrates that treating the injured spinal cord with ChABC alone was sufficient to achieve the modification of the astrocytic reaction described by Chau and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…When applied to an acute cervical dorsal column crush lesion, ChaseABC enhances axonal regeneration and locomotor and proprioceptive recovery in these animals, demonstrating that in vivo ChaseABC delivery can lead to anatomical and functional recovery (Bradbury et al, 2002). Regeneration of sensory axons and also axons in Clarke's nucleus after hemisection injury was also observed following ChaseABC treatment (Yick et al, 2003;Shields et al, 2008). Acute and delayed intrathecal ChaseABC infusion to a rubospinal tract lesion reduced the atrophy of neuronal cell bodies of the rubospinal neurons, suggesting a neuroprotective role for ChaseABC (Carter et al, 2011).…”
Section: Ecm and Pnns In Cns Injuriesmentioning
confidence: 92%
“…In keeping with the interest in ChABC's putative mechanism of action, 13 of the 24 studies were solely focused on anatomical=histologic outcomes, with no measurement of behavioral outcome (Carter et al, 2008;Chau et al, 2004;Fouad et al, 2009;Iaci et al, 2007;Ikegami et al, 2005;Iseda et al, 2008;Massey et al, 2006Massey et al, , 2008Shields et al, 2008;Tan et al, 2006;Tom and Houlé, 2008;Vavrek et al, 2007;Xia et al, 2008;Yick et al, 2003). In general, independent laboratories report ChABC promoting increased axonal sprouting (particularly serotonergic fibers) using either anterograde or retrograde tracing techniques.…”
Section: Chondroitinase Abcmentioning
confidence: 99%
“…In general, independent laboratories report ChABC promoting increased axonal sprouting (particularly serotonergic fibers) using either anterograde or retrograde tracing techniques. As an adjunct treatment to a transplantation therapy (e.g., Schwann cells, peripheral nerve graft), ChABC reportedly improved axonal growth and=or serotonergic sprouting (Chau et al, 2004;Fouad et al, 2005;Houle et al, 2006;Shields et al, 2008;Tom and Houlé, 2008). Xia and colleagues (2008) reported a reduced cystic cavity, suggestive of some neuroprotective effect.…”
Section: Chondroitinase Abcmentioning
confidence: 99%